A new classification algorithm for discrimination of ventricular from supraventricular tachycardia in a dual chamber implantable cardioverter defibrillator. - Korte T; Jung W; Wolpert C; Spehl S; Schumacher B; Esmailzadeh B; Lüderitz B (Journal of Cardiovascular Electrophysiology, 1998)
Introduction: The high incidence of inappropriate therapies due to supraventricular tachycardia remains a major unsolved problem of implantable cardioverter defibrillators. We report a new detection formula for discrimination of ventricular tachycardia from supraventricular tachycardia in a patient with a dual chamber implantable cardioverter defibrillator and a new atrioventricular classification algorithm. Methods and Results: The enhanced detection algorithm performs a stepwise arrhythmia analysis. The rhythm is first classified on the basis of cycle length. Each episode is then classified as supraventricular or ventricular on the basis of atrioventricular association, stability of circle length, and origin of acceleration. Sophisticated diagnostic information is provided by atrioventricular markers and electrogram recordings. Successful discrimination of two spontaneous episodes of ventricular tachycardia and supraventricular tachycardia is demonstrated. Conclusion: This new dual chamber detection algorithm may significantly improve the specificity of tachyarrhythmia detection without sacrificing sensitivity, thereby reducing the number of spurious shocks in patients with recurrent supraventricular tachycardias. Further studies are needed to assess the sensitivity and specificity of this detection algorithm.